2018
DOI: 10.25182/jgp.2018.13.1.17-26
|View full text |Cite
|
Sign up to set email alerts
|

The application of probability method to estimate micronutrient deficiencies prevalence of Indonesian adults

Abstract: The objective of this study was to analyze micronutrient deficiencies (Ca, Fe, Zn, Vitamin A and C) of Indonesian adults using probability method (PBM) and cutoff point method (CPM). This research was conducted by analyzing secondary data from Total Diet Study of the Ministry of Health of Indonesia, obtained from 24-h food recall method. The subjects were 58, 014 adults aged 19-49 years. The nutrient requirement from Institute of Medicine were used as benchmark. Both PBM and CPM were applied to assess micronut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
0
13
0
2
Order By: Relevance
“…Tingkat kecukupan kalsium, seng dan vitamin A masih rendah. Hasil ini sejalan berdasarkan penelitian terdahulu yang menunjukkan bahwa kecukupan zat gizi mikro pada penduduk dewasa di Indonesia relatif masih rendah (39).…”
Section: Tabel 4 Asupan Gizi Dan Tingkat Kecukupan Giziunclassified
See 1 more Smart Citation
“…Tingkat kecukupan kalsium, seng dan vitamin A masih rendah. Hasil ini sejalan berdasarkan penelitian terdahulu yang menunjukkan bahwa kecukupan zat gizi mikro pada penduduk dewasa di Indonesia relatif masih rendah (39).…”
Section: Tabel 4 Asupan Gizi Dan Tingkat Kecukupan Giziunclassified
“…Penelitian di Sukabumi menunjukkan bahwa densitas protein, vitamin A, kalsium, dan vitamin C masih dibawah rekomendasi yang juga sama halnya dengan penelitian ini (29). Rendahnya konsumsi sayur, buah dan pangan hewani pada perempuan dewasa di Indonesia menjadi faktor yang mengakibatkan rendahnya densitas asupan kalsium dan vitamin, khususnya vitamin A dan C. penelitian ini sejalan dengan peneltian sebeljumnya pada subjek dewasa bahwa konsumsi sayur, buah dan pangan hewani masih rendah (31,32,39). Kekurangan zat gizi mikro dalam waktu yang panjang dapat berpengaruh terhadap penurunan tingkat kecerdasan, peningkatan penyakit infeksi, penurunan produktivitas kerja, serta dapat meningkatkan angka kematian ibu dan anak (1).…”
Section: Tabel 4 Asupan Gizi Dan Tingkat Kecukupan Giziunclassified
“…The prevalence of vitamin D deficiency for female adult is 50% and senior adult is 35.1%. 30,31 Calcium is required for the normal development and maintenance of the skeleton, as well as for the proper functioning of neuromuscular and cardiac function. It is stored in the bones and teeth, where it provides structure and strength.…”
Section: Physical Activity and Nutrition Guideline For Age 45+mentioning
confidence: 99%
“…Studies have shown the association between protein, vitamin A, vitamin C, vitamin E, vitamin D, calcium, and omega-3 with mobility problems in later life. 6 Understanding factors contributing to these mobility-related diseases, prevention strategies that emphasizing the needs for dietary intervention would be vital to reduce the disease burden in ageing population.…”
Section: Introductionmentioning
confidence: 99%